Examining The Interplay of Government Policies, University Support, and Industry Involvement in Driving Startup Performance and Economic Growth Through Innovation Capacity and Entrepreneurial Skills Development - Khan, Muhammad Asif; Pangaribuan, David; Nuryati, Tutty; Syamil, Ahmad (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Startups were pivotal drivers of innovation and economic growth, yet they faced systemic challenges such as limited funding, market volatility, and skill gaps. While government policies, universities, and industries individually supported entrepreneurial ecosystems, their combined impact and mediating mechanisms remained underexplored. This study addressed this gap by introducing the Triplex Model, which investigated how governmental initiatives, academic support, and industrial participation synergistically enhanced startup performance and economic development.Purpose: Our study introduces the Triplex Model, which investigates the dynamic interplay between governmental policies, academic support, and industrial participation in driving startup performance and economic growth. It focuses on the mediating roles of innovation capacity and entrepreneurial skill enhancement within this context.Design/methodology/approach: A structural equation modelling (SEM) approach was utilized to analyze data from 762 startup founders across Indonesia, Malaysia, and Singapore. The study integrated Systems of Innovation Theory and the Triple Helix Model to provide a robust theoretical framework for understanding entrepreneurial ecosystems.Findings/Result: The analysis reveals that governmental initiatives, university support, and industry involvement significantly influence startup success and economic expansion through the intermediary roles of innovation capacity and entrepreneurial skill enhancement. These findings highlight the critical importance of a collaborative and synergistic approach to fostering innovation and entrepreneurship.Conclusion: Our study offered valuable insights for policymakers, academic institutions, and industry leaders. It underscored the need to foster collaborative environments, align strategic initiatives with innovation-driven objectives, and strengthen entrepreneurial ecosystems to promote sustainable economic development.Originality/value: This study comprehensively examines external support mechanisms within entrepreneurial ecosystems. By synthesizing Systems of Innovation Theory and the Triple Helix Model, the study extends their applicability and bridges theoretical and practical knowledge gaps, presenting a strategic blueprint for advancing innovation-led entrepreneurship. Keywords: government policies, industry involvement, university support, entrepreneurial skill development, startup performance